Inflammatory granulomatous mastitis caused by Corynebacterium kroppenstedtii: A clinical challenge: Challenge of C. kroppenstedtii induced mastitis. (July 2022) - Brouwer de Koning, I.M.; Lemson, A.; Renders, N.H.M.; Bessems, M.; Nooijen, P.T.G.A.; Draaisma, W.A.; Bosscha, K.
Highlights: It is important to rule out a malignancy as soon as possible in case of mastitis. The diagnostic process of Corynebacterium kroppenstedtii is a real challenge. Anaerobe culturing should be added to the standard diagnostic procedure in mastitis. Abstract: Background: Corynebacterium induced granulomatous mastitis is a rare inflammatory condition of the breast, generally occurring in parous reproductive-aged women, that could simulate inflammatory breast cancer. Therefore, it is important to rule out the diagnosis of cancer because treatment consists of long-term antibiotics or, in case of clinical deterioration, surgical procedures. However, excluding a malignancy and determining a Corynebacterium induced mastitis is a diagnostic challenge. Case report: Three patients with mastitis caused by Corynebacterium kroppenstedtii were described: a patient with a unilateral painful mass with abscess formation later, a patient with recurrent mastitis for months with a sudden progression and a patient with persisting mastitis despite antibiotic treatment. Results: Preoperative imaging reduced the possibility of, but was unable to exclude, a malignancy. Multiple and/or deep biopsies were needed to confirm granulomatous mastitis and extensive staining was needed to find Corynebacterium kroppenstedtii . Conclusion: Because clinical and/or radiological features are insufficient to prove Corynebacterium induced granulomatous mastitis, core-needle or surgical biopsies remain the cornerstone of the diagnosis together with extensive (beyond Gram) staining looking for Corynebacterium subspecies.